Who Votes among Asian American Ethnic Subgroups? - Haifan Xiao; Loretta E. Bass (Socius, 2021)
The authors address the gap in what is known about voting among Asian American ethnic subgroups using National Asian American Survey 2016 Post-Election Survey data to investigate the propensity to vote in the 2016 presidential election across two samples: registered Asian Americans and registered naturalized Asian Americans. The authors use logistic regressions to examine voting behavior across 10 Asian ethnic subgroups for the first time. Across both samples of Asian Americans and naturalized Asian Americans, Chinese Americans demonstrate a lower propensity to vote than most other Asian ethnic subgroups, while Asian Indian and Bangladeshi Americans demonstrate a higher propensity to vote. Among all Asian Americans, being female, being older, and having more education all pattern higher rates of reported voting in the 2016 presidential election, while for naturalized Asians, time in the United States and higher levels of education are associated with a higher likelihood of voting in the 2016 presidential election.